42.4k views
5 votes
3x + 2y - z= 7This system has three equations: {-3x + y + 2z = -143x + y -z = 101. Add the first two equations to get a new equation.2. Add the second two equations to get a new equation.3. Solve the system of your two new equations.4. What is the solution to the original system of equations?

3x + 2y - z= 7This system has three equations: {-3x + y + 2z = -143x + y -z = 101. Add-example-1
User Gkb
by
5.8k points

1 Answer

2 votes

We are given the following system of equations:


\begin{gathered} 3x+2y-z=7,(1) \\ -3x+y+2z=-14,(2) \\ 3x+y-z=10,(3) \end{gathered}

1. We will add equation (1) and equation (2), we get:


3x+2y-z-3x+y+2z=7-14

Now we add like terms:


3y+z=-7,(4)

We get a new equation which we called equation (4).

2. Now, we will add equation (2) and equation (3), we get:


-3x+y+2z+3x+y-z=-14+10

Now, we add like terms:


2y+z=-4,(5)

We get a new equation that we called equation (5).

3. equation (4) and equation (5) form a new system of equations:


\begin{gathered} 3y+z=-7,(4) \\ 2y+z=-4,(5) \end{gathered}

To solve the system we will subtract equation (5) from equation (4), this way we will be able to cancel out the variable "z". Like this:


3y+z-2y-z=-7+4

Now, we add like terms:


y=-3

Therefore, the value of "y" is -3.

Now, we substitute the value of "y" in equation (4), we get:


3(-3)+z=-7

Solving the product:


-9+z=-7

Now, we add 9 to both sides:


\begin{gathered} -9+9+z=-7+9 \\ z=2 \end{gathered}

Therefore, we have the following values from the new system:


\begin{gathered} y=-3 \\ z=2 \end{gathered}

4. To determine the values of the original system we will substitute the values of "y" and "z" in equation (1):


3x+2(-3)-(2)=7

Solving the operations we get:


\begin{gathered} 3x-6-2=7 \\ 3x-8=7 \end{gathered}

Now, we will add 8 to both sides:


\begin{gathered} 3x-8+8=7+8 \\ 3x=15 \end{gathered}

Now, we will divide both sides by 3:


x=(15)/(3)=5

Therefore, the solution of the system is:


(x,y,z)=(5,-3,2)

User YoniChechik
by
6.0k points